The Effect Investment, Funding, and Dividend Policy Toward the Company Value - Syahri, Alfi; Robiyanto, Robiyanto (Universitas Pendidikan Ganesha, 2020)
This study aims to analyze the effect of financial policy consisting of investment policies proxied by Total Asset Growth (TAG) and Market Book to Asset (MBAR), funding policies proxied by Debt to Equity Ratio (DER) and dividend policies proxied by the Dividend Payout Ratio (DPR) on the value of companies proxied by Price to Earning Ratio (PER) and Price to Book Value (PBV). The research method used in this study is panel regression analysis. Furthermore, the data in this study presented as quantitative data. The data is taken from secondary data in the form of panel data listed from 2015 to 2018 research periods. The findings showed that financial policy has a significant impact on firm value.